Renegades Write the Rules : How the Digital Royalty use Social Media to Innovate - Martin, Amy Jo, 1979- (San Francisco Jossey-Bass, 2012)
Learn the rules to building loyal (and lucrative) digital followings Renegades Write the Rules reveals the innovative strategies behind the social media success of today s top celebrities, brands, and sports icons, and how you can follow their lead.
Include Index and Illustration
Keywords: Social media -- Digital communications--Social aspects -- Internet in public relations